A practical strategy to design and develop an isoform-specific fluorescent probe for a target enzyme: CYP1A1 as a case study. Issue 4 (6th February 2017) - Dai, Zi-Ru; Feng, Lei; Jin, Qiang; Cheng, Hailing; Li, Yan; Ning, Jing; Yu, Yang; Ge, Guang-Bo; Cui, Jing-Nan; Yang, Ling
Abstract : A practical strategy was proposed and successfully used to design and develop an isoform-specific probe for a given enzyme. Abstract : The development of isoform-specific probe(s) for a target enzyme with multiple homologs is always challenging. Herein, a practical strategy was used to design and develop an isoform-specific probe for CYP1A1, a key cytochrome P450 isoenzyme involved in xenobiotic metabolism and bioactivation. On the basis of the subtle differences in 3D structure and substrate preference between CYP1A1 and its homolog CYP1A2, we proposed that it was possible to design a CYP1A1-specific probe via local modification of the reaction site on known CYP1A substrates. To validate this hypothesis, 4-hydroxy-1, 8-naphthalimide (HN ) was selected as the basic fluorophore due to its excellent optical properties, while a series of O -alkylatedHN derivatives were prepared to evaluate their specificity towards CYP1A1. Our results revealed that the introduction of a chloroethyl toHN could get the best isoform selectivity towards CYP1A1 over other CYPs including CYP1A2. The newly developed probeNBCeN exhibited excellent specificity, high sensitivity, and a ratiometric fluorescence response following CYP1A1-catalyzed O -dechloroethylation.NBCeN was successfully used to real-time monitor the activity of CYP1A1 in complex biological samples and to rapidly screen CYP1A1 modulators in living systems.NBCeN could also be used for two-photon imaging of intracellular CYP1A1 in living cells and tissues with high ratiometric imaging resolution and deep tissue penetration. All these findings demonstrated that local modification of non-specific substrates was a practical strategy to develop an isoform-specific probe for a target isoenzyme, whileNBCeN could serve as a specific imaging tool to explore the biological functions of CYP1A1 in complex biological systems.